Usefullness of Choyoto for Hand Eczema - NIIZAWA, Atsushi; TAKAYA, Yutaka; TAHARA, Eiichi; NAKAO, Kikuyo; SHINTANI, Takuhiro; MORIYAMA, Kenzo; TSUKIOKA, Yasuyuki; NINOMIYA, Hiroyuki (Kampo Medicine, 2006)
We analyzed the differences between responder and non-responder groups using Choyoto for hand eczema. In 7 cases the drug was effective, and in 6 cases it was not. Most patients in the effective group had white-complexioned skin, and the eczema tended to localize on the hands. In contrast, most patients in the non-effective group had with sleep difficulties and/or a smoking habit. In addition, they showed marked symptoms of Oketsu such as dark red gingiva, indicating that many of the non-effective hand eczema cases had elevated Oketsu scores. It was shown that objective and subjective symptoms could be indicators for the choosing of Choyoto for hand eczema treatment.